Auslegungsstrategie für Hochleistungs-LED-Systeme auf Basis wärmeleitender Kunststoffe - Fischer, Andreas; Ranft, Florian; Drummer, Dietmar (VDI - Kunststoffe in Optischen Systemen, 2014)

Effect of fillers on the metallization of laserstructured polymer parts - Fischer, Andreas; Meister, Steve; Drummer, Dietmar (Journal of Polymer Engineering, 2016)
UnivIS-Import:2017-01-09:Pub.2016.tech.FT.FT-KT.effect

Effect of fillers on the metallization of laser-structured polymer parts - Fischer, Andreas; Meister, Steve; Drummer, Dietmar (Journal of Polymer Engineering, 2017)
Keywords: Laser direct structuring; Molded interconnect devices; Plating; Talc

Effect of flow lines on the metallization of laser structured polymer parts - Fischer, Andreas; Kuhn, Thomas; Müller, Hagen; Drummer, Dietmar; Franke, Jörg; Zimmermann, Andre (SPE Proceedings Antec, 2017)

Effect of graphite on the flame retardancy and thermal conductivity of P-N flame retarding PA6 - Zhang, Luchong; Wang, Liang; Fischer, Andreas; Wu, Wei; Drummer, Dietmar (Journal of Applied Polymer Science, 2018)

Effect of talc on the metal adhesion of laser-structured polymer parts - Fischer, Andreas; Kuhn, Thomas; Drummer, Dietmar; Franke, Jörg (13th International Congress Molded Interconnect Devices, 2018)

Effects of CNTs/BN Hybrids on the Thermal Conductivity of PA6 Composite and Its Mechanism 碳纳米管/氮化硼混杂填料对尼龙6导热性能的影响及其机理 - Wang, Liang; Wu, Wei; Zou, Zhiqiang; Liu, Jiang; Fischer, Andreas; Drummer, Dietmar (Gaofenzi Cailiao Kexue Yu Gongcheng/Polymeric Materials Science and Engineering, 2019)
Polyamide 6/hexagonal boron nitride(PA6/BN) composites were firstly prepared by melt blending. After determining the optimal dosage of BN according to the thermal conductivity of the composites, carbon nanotubes and compatilizer were further introduced into the PA6/BN blends. The thermal conductivity test, DSC, DMA and SEM were carried out to investigate effects of CNTs/BN hybrids on properties of the PA6 composites, and the corresponding three-dimensional heat transfer models were proposed to explain their thermal conduction mechanism. The results show that CNTs/BN(2%/20.83%) hybrids could dramatically enhance the thermal conductivity of the PA6 composites, the thermal conductivity value is 0.76 W/(m•K), 2.45 times of pure PA6. Meanwhile, the DMA results and SEM images agree well with the proposed model. The thermal conductive PA6 composites are promising to be used as appliance materials.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Hybrids; Polyamide 6; Thermal conductivity; Three-dimensional heat transfer model

Enhanced thermal conductivity and flame retardancy of polyamide 6/flame retardant composites with hexagonal boron nitride - Wang, Liang; Zhang, Luchong; Fischer, Andreas; Zhong, Yuhua; Drummer, Dietmar; Wu, Wei (Journal of Polymer Engineering, 2018)

Entwicklung neuartiger Hochleistungs-LED-Systeme auf Basis wärmeleitender Kunststoffe - Ranft, Florian; Fischer, Andreas; Drummer, Dietmar (SMT 2013 - MID Forum, 2013)

Flame retarding mechanism of Polyamide 6 with phosphorus-nitrogen flame retardant and DOPO derivatives - Li, Maolin; Zhong, Yuhua; Wang, Zheng; Fischer, Andreas; Ranft, Florian; Drummer, Dietmar; Wu, Wei (Journal of Applied Polymer Science, 2016)
A novel flame-retardant composite was prepared by introducing a phosphorus-nitrogen flame retardant and DOPO-SiO2 into PA6. DOPO-SiO2 was synthesized successfully in a one-step process. PA6/OP1314/DOPO-SiO2 achieved a UL 94 V-0 rating with an LOI value of 31%. The maximum mass loss rate of decomposition decreased significantly and char residue increased to 11.6 wt % compared with that of pure PA6. The compacted and dense char was formed due to the combination of the P-N flame retardant and DOPO-SiO2. The complex viscosity of PA6/OP1314/DOPO-SiO2 increased considerably which tend to prevent the dripping phenomenon. The flame-retardant mechanism of PA6/OP1314/DOPO-SiO2 was also investigated by Fourier transform infrared spectroscopy FTIR at different temperatures and the pyrolysis products were investigated by pyrolysis gas chromatography/ mass spectrum (Py-GC/MS). It was assumed that DOPO-SiO2 and the hypophosphite of OP1314 possess excellent flame retardancy during the gaseous phase. Meanwhile, melamine and phosphate reacted with the pyrolytic products of PA6 to protect the matrix during the condensed phase.
UnivIS-Import:2016-06-01:Pub.2016.tech.FT.FT-KT.flamer
Keywords: polyamides; spectroscopy; thermogravimetric analysis (TGA)

Heat propagation in thermally conductive polymers of PA6 and hexagonal boron nitride - Fischer, Andreas; Zhong, Yuhua; Zhang, Luchong; Wu, Wei; Drummer, Dietmar (Fire and Materials, 2019)
Thermally conductive polymers offer new possibilities for the heat dissipation in electric and electronic components, for example, by a three-dimensional shaping of the heat sinks. To face safety regulations, improved fire performance of those components is required. In contrast to unfilled polymers, those materials exhibit an entirely different thermal behavior. To investigate the flammability, a phosphorus flame retardant was incorporated into thermally conductive composites of polyamide 6 and hexagonal boron nitride. The flame retardant decreased the thermal conductivity only slightly. However, the burning behavior changed significantly, due to a different heat propagation, which was investigated using a thermographic camera. An optimum content of hexagonal boron nitride for a sufficient thermal conductivity and fire performance was found between 20 and 30 vol%. The improvement of the fire performance was due to a faster heat release out of the pyrolysis zone and an earlier decomposition of the flame retardant. For higher contents of hexagonal boron nitride, the heat was spread faster within the part, promoting an earlier ignition and increasing the decomposition rate of the flame retardant.
CRIS-Team Scopus Importer:2019-08-13
Keywords: aluminum diethylphosphinate; hexagonal boron nitride; polyamide 6; thermally conductive polymers; thermography

Influencing factors on field inversion in HVDC cables - Fuchs, Karsten; Berger, Frank; Fischer, Andreas; Drummer, Dietmar (Achter Workshop Optische Technologien - LED Beleuchtung - Technik und Anwendung, 2015)
UnivIS-Import:2016-06-01:Pub.2015.tech.FT.FT-KT.influe_6

Polymer films for laser-structured circuit carriers - Fischer, Andreas; Drummer, Dietmar (12th International Congress on Molded Interconnect Devices, MID 2016, 2016)
Keywords: Films; Laser direct structuring; Molded-Interconnect-Devices; Plating; Talc

Reliability of LDS Conductor Paths - Influencing Factors and Characterization Methods - Fischer, Andreas; Müller, Hagen; Kuhn, Thomas; Drummer, Dietmar; Kück, Heinz; Franke, Jörg (11th International Congress Molded Interconnect Devices, 2014)
Keywords: 3D-MID; E|P; Elektronikproduktion; Zuverlässigkeit

The effect of hBN on the flame retardancy and thermal stability of P-N flame retardant PA6 - Zhong, Yuhua; Zhang, Luchong; Fischer, Andreas; Wang, Liang; Drummer, Dietmar (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2017)

Thermally Conductive Polymers Meet LED - Drummer, Dietmar; Fischer, Andreas; Ranft, Florian; Heinle, Christoph; Amesöder, Simon; Lober, Andreas (Kunststoffe International, 2017)
UnivIS-Import:2017-07-10:Pub.2017.tech.FT.FT-KT.therma

Wärmeleitender Kunststoff trifft LED - Drummer, Dietmar; Fischer, Andreas; Ranft, Florian; Heinle, Christoph; Amesöder, Simon; Lober, Andreas (Kunststoffe, 2017)
UnivIS-Import:2017-03-24:Pub.2017.tech.FT.FT-KT.wrmele